Effects of operating parameters of impinging stream dryer on parboiled rice quality and energy consumption. Issue 5 (3rd April 2020) - Kumklam, Ponlakrit; Prachayawarakorn, Somkiat; Devahastin, Sakamon; Soponronnarit, Somchart
Abstract: It is very important to know how operating condition of a coaxial impinging stream dryer affects the drying time, parboiled rice quality and energy consumption. The drying temperature, parboiled paddy feed rate, drying air velocity and impinging distance were experimentally investigated. Increases in drying temperature and air velocity and a decrease in paddy feed rate provided higher evaporation rate whilst impinging distance, ranging from 5 to 13 cm, did not affect the evaporation rate. Collision between kernels within the impinging zone caused the hull's lemma splitting from the kernel and the percentage of the split kernel strongly depended on the air velocity and feed rate. The acceleration in the rate of drying by changing the above operating parameters did not affect the head rice yield. In addition, the collision of kernels also did not influence the head rice yield since the mechanical properties of rice are strengthened during steaming step in the parboiling process. However, the change of head rice quality was only governed by the moisture content after drying. The total energy consumption including electricity and heat was strongly depended on the air velocity and feed rate whilst it was slightly changed with the drying temperature. From the present study, it was recommended that the parboiled paddy should not be dried below 25% d.b. and the highest temperature that could possibly be used was 190 °C and the inlet air velocity should not be below 15 m/s.